Assessing the influence of information, education and communication (IEC) strategies in the prevention of malaria in pregnancy in Ejisu-Juaben District of Ghana - Adjei, Rose Odotei (2011)
A thesis submitted to the College of Health Sciences in partial fulfilment of the requirements for Master of Science degree (Community Health).